LA ECONOMÍA DE ENCLAVE FORESTAL: LA CONFIGURACIÓN CAPITALISTA DEL PAISAJE EN PUERTO MORELOS, QUINTANA ROO, MÉXICO (1902-1936). - Cruz Coria, Erika (2011)
The explanation of the landscape configuration of Puerto Morelos that is presented in this paper covers the first three decades of existence of this town (1902 -1936), which correspond to the period in which the capital -by means of foreign companies exploiting gum- launched dynamic penetration and subsumption on this town that triggered processes of material production and social reproduction that led to the configuration of a landscape with characteristics of forest enclave that have been simmering in the federal territory of Quintana Roo, México from late nineteenth century.